Điều chế một số chất lỏng ion tetrafluoroborat 1-n-alkil-3-metilimidazolium trong điều kiện hóa học xanh - Thạch, Lê Ngọc; Mai Phương, Nguyễn Thị (Vietnam Journal of Chemistry, 2014)
In this paper we described the preparation of some 1-n-alkyl-3-methylimidazolium tetrafluoroborates ([Cnmim]BF4 with Cn is ethyl, n-butyl, n-hexyl, n-octyl respectively) in Green Chemistry conditions. All starting materials were used in stoichiometric quantities; the reactions were activated by microwave or ultrasound in solventless media. Firstly, alkylimidazolium bromides were prepared from the N-alkylation of N-methylimidazole with a n-alkyl bromide corresponding. After that, tetrafluoroborate furnished a metathesis with bromide to give the final products. Comparing with conventional heating, the obtained yield was higher and the reaction time was shorter under microwave irradiation.